THE SIGNIFICANCE OF QUANTITATIVE JOB DEMANDS AND PSYCHOLOGICAL FATIGUE AND THEIR IMPACT ON BEHAVIORAL COMMITMENT VOLATILITY STUDY PT. BANK MANDIRI (PERSERO) MAGELANG BRANCH - Aditya Angger Wibowo (WORLDVIEW ( Development economic and sharia studies journal ), 2026)
This research aims to empirically examine the determination of quantitative job demands and psychological burnout on the existence of behavioral commitment volatility. The analytical focus is directed toward unraveling the extent to which operational workload pressures and the degradation of employee mental health can predict fluctuations in actual behavioral loyalty within the financial services ecosystem. The locus of this study is specifically contextualized among banking practitioners operating under PT Bank Mandiri (Persero) Tbk, Magelang Branch. To achieve this objective, a causal-quantitative design was applied, involving 141 branch office personnel as research participants. Primary data collection was executed through a structured questionnaire instrument, with subject recruitment determined via a proportionate stratified random sampling technique to ensure representation across all organizational strata. The accumulated empirical data were statistically tested using multiple linear regression analysis computed through IBM SPSS Statistics Version 31. The primary findings from the regression modeling demonstrate that quantitative job demands and psychological burnout, both partially and simultaneously, play a positive and significant role in driving the acceleration of behavioral commitment volatility. This discovery underscores that the combination of rigid quantitative target pressures and the collapse of emotional resilience acts as a core generator disrupting the stability of daily employee compliance behaviors. The practical implications of this study obligate banking management to immediately restructure workload management frameworks through a psychosocial risk mitigation approach to suppress employee withdrawal behavior intentions.